Programa de capacitación para desarrollar las competencias tecnológicas de los docentes en el proceso de enseñanza - aprendizaje en el nivel de educación básica en la escuela “Juan Ramón Jiménez”, durante el periodo 2012-2013 - Abad Martínez, María del Cisne (2015)
The incorporation of technological competence in the education system is currently in the process of retrofitting the Ministry of Education of Ecuador is revitalizing the preparation especially for teachers in order to possess the skills necessary to function with ease and enhance the educational use, since the teaching with the use of technology enhances learning in any area of study and manages to prepare students with new technology skills. Based on this urgent need to improve the main research question arose: How to develop the technological skills of teachers in the teaching-learning process at the level of basic education in the school "Juan Ramon Jimenez". Historic logical analysis: to effect the treatment of this problem a number of techniques where design diagnostic and experimental applied taking into account the following authors Rodriguez Moreno Vazquez & Mulet (2014) report on the theoretical methods proposed and synthesis, deductive hypothetical and empirical methods: survey and document review. (Rodriguez et al., 2014). Consistent with the foregoing, the following general objective was raised: Design a training program to develop the technological skills of teachers in the teaching-learning process on the level of Basic Education "Juan Ramon Jimenez" School. One of the important conclusions was established after finding diagnostic results is detected that teachers develop a limited technological skills in relation to lack of training, use of sources of information, technological, management Word and Excel programs; therefore, as part of research and improvement proposal a training program aimed at teachers working at the school, developed the same as it was accepted by those present during the period of 5 weeks through workshops in which important and significant results obtained demonstrating that applying technologies strengthens the teaching-learning process and allows for greater interactivity of the student and suppress traditional classes using the board as a teaching resource and lecture